Pengelolaan Pesan Parodi Melalui Media Sosial Instagram - Efin Harfy Hilmiawan; Erik Setiawan (UNISBA Press, 2024)
Abstract. Traffic conditions in the city of Bandung are still very closely related to violations committed by road users due to a lack of awareness when driving. This problem prompted the Bandung City government through the Bandung City Transportation Department to create a program that is able to monitor road users to ensure traffic order through the ATCS (Area Traffic Control System) program. Bandung City Transportation Agency ATCS often posts parody content taken from incidents of violations committed by road users in Bandung City. Parody content like this is intended to provide information and advice to the public not to commit violations and to build public traffic awareness. This research aims to explain and analyze the management of parody messages as a strategy in building traffic compliance in the city of Bandung via the social media Instagram. This study uses a qualitative descriptive approach to observe the process of managing parody messages implemented by the Instagram account @atcs.kotabandung. The data collection method uses observation of posted content, analysis of message content, as well as interviews with account managers and documentation of parody content owned by ATCS Bandung City. It is hoped that this research will show that managing parody messages can be an effective means of increasing traffic compliance by conveying informative and educational messages creatively and entertainingly. It is hoped that this research can provide additional insight regarding the potential use of social media, especially Instagram, in supporting the efforts of the government and the Bandung City Transportation Department in building traffic awareness and compliance in Bandung City. Abstrak. Kondisi lalu lintas di Kota Bandung masih sangat erat dengan pelanggaran yang dilakukan oleh para pengguna jalan karena kurangnya kesadaran dalam berkendara. Permasalahan ini yang mendorong pemerintah Kota Bandung melalui Dishub Kota Bandung untuk menciptakan suatu program yang mampu memonitor para pengguna jalan agar tewujudnya ketertiban lalu lintas melalui program ATCS (Area Traffic Control System). ATCS Dishub Kota Bandung sering memposting konten parodi yang diambil dari kejadian-kejadian pelanggaran yang dilakukan oleh pengguna jalan di Kota Bandung, Koten parodi seperti ini ditujukkan untuk memberikan informasi serta imbauan kepada masyarakat untuk tidak melakukan pelanggaran dan untuk membangun kesadaran lalu lintas masyarakat.Penelitian ini bertujuan untuk memaparkan serta menganalisis pengelolaan pesan parodi sebagai strategi dalam membangun kepatuhan berlalu lintas di Kota Bandung melalui media sosial Instagram. Studi ini menggunakan pendekatan deskriptif kualitatif untuk mengamati proses pengelolaan pesan parodi yang diimplementasikan oleh akun Instagram @atcs.kotabandung. Metode pengumpulan data menggunakan observasi terhadap konten yang diposting, analisis konten pesan, serta wawancara dengan pengelola akun tersebut dan dokumentasi pada konten-konten parodi yang dimiliki oleh pihak ATCS Kota Bandung. Dari penelitian ini diharapkan menunjukan bahwa pengelolaan pesan parodi dapat menjadi sarana yang efektif untuk mengingkatkan kepatuhan berlalu lintas dengan menyampaikan pesan informatif serta edukatif secara kreatif dan menghibur. Penelitian ini diharapkan dapat memberikan wawasan tambahan terkait potensi penggunaan media sosial, khususnya Instagram dalam mendukung upaya pemerintah dan Dinas Perhubungan Kota Bandung dalam membangun kesadaran dan kepatuhan berlalu lintas di Kota Bandung.Kata kunci: Pesan, Parodi, Kepatuhan Berlalu Lintas, Instagram ABSTRACTTraffic conditions in the city of Bandung are still very closely related to violations committed by road users due to a lack of awareness when driving. This problem prompted the Bandung City government through the Bandung City Transportation Department to create a program that is able to monitor road users to ensure traffic order through the ATCS (Area Traffic Control System) program. Bandung City Transportation Agency ATCS often posts parody content taken from incidents of violations committed by road users in Bandung City. Parody content like this is intended to provide information and advice to the public not to commit violations and to build public traffic awareness. This research aims to explain and analyze the management of parody messages as a strategy in building traffic compliance in the city of Bandung via the social media Instagram. This study uses a qualitative descriptive approach to observe the process of managing parody messages implemented by the Instagram account @atcs.kotabandung. The data collection method uses observation of posted content, analysis of message content, as well as interviews with account managers and documentation of parody content owned by ATCS Bandung City. It is hoped that this research will show that managing parody messages can be an effective means of increasing traffic compliance by conveying informative and educational messages creatively and entertainingly. It is hoped that this research can provide additional insight regarding the potential use of social media, especially Instagram, in supporting the efforts of the government and the Bandung City Transportation Department in building traffic awareness and compliance in Bandung City.